A practical method for the evaluation of the Joule Thomson effects to predict flowing temperature profile in gas producing wells - Tarom, N.; Hossain, Mofazzal (Elsevier, 2015)
Accurate evaluation of Joule Thomson Coefficient (JTC) is important for the prediction of flowing temperature profile in a gas producing well. The evaluation of JTC requires the determination of derivative of gas compressibility factor with respect to change in temperature at constant pressure (i.e. (∂Z/∂T)p). This may be determined using an appropriate Equations of States (EOS) for a given gas mixture where compositions details are known. In many cases, the details of gas compositions and its associated properties are not known, especially at the appraisal stage. In this study, a simplified practical method has been developed to predict the JTC. This paper presents details of the mathematical model based on which the proposed method is developed. The terms Z and (∂Z/∂T)p have been predicted for a number of gas mixtures using proposed method, and compared the results with those obtained using Peng–Robinson Equation of State (PR EOS) and HYSYS software to provide the accuracy of this work for evaluation of compressibility factor for gas mixtures. The results showed close agreement between two methods. The model is applied to represent gas field in order to predict the temperature profile for gas production wells. A sample case study has been carried out to investigate the flowing temperature profile along a gas producing well. It is demonstrated that the proposed method can be reliably used for evaluation of well following temperature profile along gas producing wellbores.